Contractor Selection Criteria Factors PT. The Influence Of Wasis Nugraha's Works Performance of The Tlogomas Family Bridge Construction Project, Malang City - Nurcholis, Mochamad; Witjaksana, Budi; Teki Tjendani, Hanie (Green Publisher Indonesia, 2023)
The success of project performance is the main target for companies engaged in construction services. Considering how complicated and complex a construction project is, a good management function is needed so that it is necessary to choose the right contractor services. Therefore, a study was conducted to determine the criteria for selecting contractors that affect project performance. The method used in this research is a quantitative descriptive approach through a case study model. The sample of this research are employees of PT. Wasis Karya Nugraha who knows the conditions and is directly involved in the work of the Tlogomas Bridge construction projects Kel. Tlogomas Malang City as many as 107 people. Data collection techniques with the method of distributing questionnaires. Data management in this study uses the Partial Least Squeare (PLS) analysis tool. The results of the research show that the criteria for selecting contractors which include contextual performance, task performance, and network have an effect on project performance. The influence of the relationship between contractor selection criteria and project performance is high. The strategy that can be used in selecting a contractor according to the criteria that influence it is to consistently pay attention to the factors in selecting a contractor. For other researchers who want to research the same research, it is better to use other factors that can affect project performance